Tijdens een soldariteitsbazar op het lentes terrein. Uit: archief F. Domela Nieuwenhuis, map VI, a, 1, A, nr. 12
Tijdens een soldariteitsbazar op het lentes terrein. Uit: archief F. Domela Nieuwenhuis, map VI, a, 1, A, nr. 12.